2008
DOI: 10.1089/gte.2007.0095
|View full text |Cite
|
Sign up to set email alerts
|

Determination of HER-2/Neu Status in Hepatocellular Carcinoma Cases

Abstract: Specific chromosome abnormalities and genetic changes in hepatocellular carcinoma (HCC) have been demonstrated by conventional cytogenetic studies or molecular cytogenetic approaches like comparative genomic hybridization and loss of heterozygosity analyses. HER-2/Neu amplification and expression has been studied as a molecular target for treatment of HCC, and there are conflicting results. We aimed to determine HER-2/Neu status in archive materials of HCC patients by fluorescence in situ hybridization (FISH).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…Previous studies have confirmed the high expression of ErvB-2 and ErbB-3 in cervical cancer tissues (Bacaksiz et al, 2008). This study found that the ErbB-3 binding protein Ebp1 is also highly expressed in cervical cancer tissues, suggesting that Ebp1 might be associated with the formation and development of cervical cancer.…”
Section: Discussionsupporting
confidence: 81%
“…Previous studies have confirmed the high expression of ErvB-2 and ErbB-3 in cervical cancer tissues (Bacaksiz et al, 2008). This study found that the ErbB-3 binding protein Ebp1 is also highly expressed in cervical cancer tissues, suggesting that Ebp1 might be associated with the formation and development of cervical cancer.…”
Section: Discussionsupporting
confidence: 81%
“…HER-2 amplification has been reported in breast cancer, and a monoclonal antibody trastuzumab, has become an important therapeutic option for patients with HER-2 amplification (44). However, reports on the status of HER-2 in HCC are conflicting (45)(46)(47)(48). By FISH, we showed a high frequency of deletion for TP53.…”
Section: Detection Of Afp Mrnamentioning
confidence: 62%
“…Amplification of HER-2 was observed in 2 patients with higher CTC counts among the 11 patients analyzed. Such amplifications are uncommon in primary tumors of HCC (45,46), whereas some studies show frequent HER-2 overexpression in HCC (47,48). The frequency of HER-2 amplification of CTCs in HCC needs to be investigated with more patients so as to clarify whether it could be a candidate gene for targeted therapy in HCC.…”
Section: Detection Of Afp Mrnamentioning
confidence: 99%
“…The EGFR is a member of a family of four closely related receptors: EGFR (ErbB-1), HER-2/neu (ErbB-2), HER-3 (ErbB-3) and HER-4 (ErbB-4). Interestingly, the expression of HER may play a role in the invasion, metastasis and progression of HCC (Bacaksiz et al, 2008;Zhang et al, 2010;Xu et al, 2011). Therefore, whether RHBDD1 participates in the above signaling pathways during HCC development remains wide open.…”
Section: Discussionmentioning
confidence: 99%